Trabajo Social y casos de exclusión familiar del adulto mayor del Barrio La Florida, parroquia El Ingenio, en la actualidad - Chuquimarca Obregon, Carmen Elizabeth (2025)
Family exclusion seriously affects the quality of life of older adults, especially those in contexts of economic and social vulnerability. This research addresses how social work intervenes in the family exclusion of older adults in Barrio La Florida, parish of El Ingenio, canton Espindola in Loja, Ecuador. It aims to analyse the causes of this exclusion, identifying its consequences and proposing strategies for social intervention. A mixed approach methodology was employed, using interviews and surveys to gather relevant information. The results showed that the exclusion of older adults responds to various factors, with family migration being one of the main causes, as many of their children or close relatives have emigrated in search of better economic opportunities, leaving older adults in situations of abandonment. In addition, it was identified that a considerable percentage of this population lacks stable economic support, both from their families and from state institutions. In the psychosocial aspect, adverse effects such as feelings of loneliness, anxiety, depression and social isolation were detected, which reinforces the need for timely interventions that prioritise the emotional well-being and reintegration of older adults in their family and community environments. In conclusion, it is highlighted that social worker intervention should focus on the promotion of community support networks, the creation of intergenerational integration programmes, the strengthening of family ties by raising awareness of the importance of accompanying older adults, and access to public health and welfare services. This research contributes to the design of strategies aimed at reducing social gaps and guaranteeing better living conditions for older adults, promoting a model of social intervention that fosters their dignity, autonomy and participation in the community